Apuntes sobre el movimiento anarquista en Perú y Bolivia, 1880-1930 - Ivanna Margarucci (Nuevo mundo - Mundos Nuevos, 2019)
In this article, we aim to make an initial approximation over the organization and struggle methods developed in Peru and Bolivia under the orientation of anarchism, during the period between the 1880s and 1930s.Adopting a transnational approach and an the comparative method, the wide time span chosen will allow us to deepen over the generalities and peculiarities that took place at certain crucial "moments" within the global experience of the libertarian movement in those two Andean region's countries.